While the town slept - Johnstone, William W. (Johnstone, William W. Tim Colter series ;, 2024)
"Wyoming Territory, 1873. Tim Colter and his trusted guide, mountain man Jed Reno, are on the trail of a vicious gang of train robbers when they happen upon a bloody and shocking scene. Lying on the ground, barely breathing, a Secret Service agent has been left for dead in the wake of a brutal ambush. His final words: "President Grant . . . assassination . . . Dugan . . . trust nobody. It's a message that chills Colter and Reno to the bone. President Ulysses S. Grant is scheduled to arrive soon in Cheyenne. Dugan is a former Confederate guerilla who leads a notorious gang of cutthroats. And the agent's last words--"trust nobody"--suggest this conspiracy could reach to the highest levels of American power. Colter and Reno are determined to stop the assassins by any means possible--even if they have to enter hell itself, better known as Dugan's Den. But to get there, they'll have to bust a lady outlaw out of prison then convince her to take them to Dugan's hideout--with a lunatic killer on their tail and the president on a collision course with death..."--